Autophagy impairment with lysosomal and mitochondrial dysfunction is an important characteristic of oxidative stress-induced senescence. Issue 1 (2nd January 2017) - Tai, Haoran; Wang, Zhe; Gong, Hui; Han, Xiaojuan; Zhou, Jiao; Wang, Xiaobo; Wei, Xiawei; Ding, Yi; Huang, Ning; Qin, Jianqiong; Zhang, Jie; Wang, Shuang; et al.
ABSTRACT: Macroautophagy/autophagy has profound implications for aging. However, the true features of autophagy in the progression of aging remain to be clarified. In the present study, we explored the status of autophagic flux during the development of cell senescence induced by oxidative stress. In this system, although autophagic structures increased, the degradation of SQSTM1/p62 protein, the yellow puncta of mRFP-GFP-LC3 fluorescence and the activity of lysosomal proteolytic enzymes all decreased in senescent cells, indicating impaired autophagic flux with lysosomal dysfunction. The influence of autophagy activity on senescence development was confirmed by both positive and negative autophagy modulators; and MTOR-dependent autophagy activators, rapamycin and PP242, efficiently suppressed cellular senescence through a mechanism relevant to restoring autophagic flux. By time-phased treatment of cells with the antioxidant N-acetylcysteine (NAC), the mitochondria uncoupler carbonyl cyanide m-chlorophenyl hydrazone (CCCP) and ambroxol, a reagent with the effect of enhancing lysosomal enzyme maturation, we found that mitochondrial dysfunction plays an initiating role, while lysosomal dysfunction is more directly responsible for autophagy impairment and senescence. Interestingly, the effect of rapamycin on autophagy flux is linked to its role in functional revitalization of both mitochondrial and lysosomal functions. Together, this study demonstrates that autophagy impairment is crucial for oxidative stress-induced cell senescence, thus restoring autophagy activity could be a promising way to retard senescence.